MEKANISME BERTAHAN MASYARAKAT TENGGER DI PROBOLINGGO TERHADAP ERUPSI GUNUNGAPI BROMO TAHUN 2010 - 2011 - , Puspita Indra Wardhani ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Bromo Volcano is one of the most active volcano in Jawa Timur. In 2010- 2011, Bromo Volcano has erupted for nine month. Tenggerâs people who live in Ngadirejo village in the Probolinggo, got the worst damage. The farming area as livelyhoods of Tenggerâs people couldnât be planted because the ash and dust covered the land until the next year. The objective from this research are learning the perception of Tenggerâs people and government to face the hazard of Bromo Volcano, analizing the effort of Tenggerâs people to face the hazard of Bromo Volcano, and formulating the coping mechanism for Tenggerâs people to face the hazard of Bromo Volcano. This research is qualitative descriptive and divided in to three steps, which are: (1) pre-fieldwork